(untitled) (Journal of Science and Technology Research, 2023)
In this study, environment-friendly, biodegradable nanocomposite has been fabricated using plasticized starch (PS) polymer and graphene oxide (GO) nanofiller. Biodegradable PS has been extracted from potatoes and a solution casting technique was used to synthesize PS/GO nanocomposite. The structural and surface morphological properties of the nanocomposite have been studied via FTIR and FESEM which demonstrate increased degree of interaction between the PS matrix and the GO nanofiller. The thermal properties of the nanocomposite showed that incorporation of GO improves the thermal stability of the nanocomposites. To study the energy storage capabilities of the PS/GO nanocomposites the electrochemical properties of the nanocomposites were as studied through cyclic voltammetry (CV), and galvanostatic charge-discharge (GCD) methods. The PS/GO nanocomposite showed improved capacitive performance with a specific capacitance of 112 F/g compared to that of pure starch (2.20 F/g) at a current density 0.1 mA/cm2. To study the effect of GO on the electrochemical properties of the nanocomposites, electrochemical impedance spectroscopy was performed and the corresponding graphs were simulated using simulation software. The incorporation of GO reduces the charge transfer resistance and thereby improve the capacitive performance. The improved electrochemical performance of the PS/GO nanocomposite can be further attributed to the large surface areas provided by the GO sheets allowing faster transport of electrolyte ions into the electrode. The result indicates that the PS/GO and nanocomposites may offer a promising route for the synthesis of bio-friendly and flexible energy storage devices. J. of Sci. and Tech. Res. 4(1): 145-154, 2022